he Analysis Of Financial Technology Effect On The Financial Performance Of Banking Sector Companies In Indonesia For 2017 - 2021 Period (Jurnal Ipteks Terapan, 2023)
Banking performance is important to analyze so that we can know the effectiveness of banks in generating profit. This research to examine the effect of internet banking, mobile banking, and ATMs on banking financial performance for the period 2017 – 2021. The type of this research is quantitative research. The characteristic of this research is descriptive. The population of this research are companies that operating in bank sector and has been registered in OJK which is 72 company.  This research have 250 samples.  The analysis model of this research is multiple linear regression. The results of the research are that internet banking positively affects bank financial performance for the 2017 – 2021 period but not significant, mobile banking positively affects bank financial performance for the 2017 – 2021 period but not significant, ATM positively affects bank financial performance for the 2017 – 2021 period but not significant